New Fatigue Provisions for the Design of Crane Runway Girders - Fisher, James M.; Van de Pas, Julius P. (Engineering Journal, 2002)
Proper functioning of bridge cranes is dependent upon proper crane runway girder design and detailing. The runway design must account for the fatigue effects caused by the repeated passing of the crane. Runway girders should be thought of as a part of a system comprised of the crane rails, rail attachments, electrification support, crane stops, crane column attachment, tie back and the girder itself. All of these items should be incorporated into the design and detailing of the crane runway girder system. Engineers have designed crane runway girders that have performed with minimal problems while being subjected to millions of cycles of loading.